2023
DOI: 10.1021/acs.chemmater.2c03006
|View full text |Cite
|
Sign up to set email alerts
|

Ligand Decomposition during Nanoparticle Synthesis: Influence of Ligand Structure and Precursor Selection

Abstract: Aliphatic amine and carboxylic acid ligands are widely used as organic solvents during the bottom-up synthesis of inorganic nanoparticles (NPs). Although the ligands’ ability to alter final NP properties has been widely studied, side reactivity of these ligands is emerging as an important mechanism to consider. In this work, we study the thermal decomposition of common ligands with varying functional groups (amines and carboxylic acids) and bond saturations (from saturated to polyunsaturated). Here, we investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 99 publications
0
7
0
Order By: Relevance
“…Previous work has shown that OLAM and OLAC may both act as reducing agents as well as surface protection and can impact the growth of nanoparticles affecting their size and shape. 28,29,39 An optimal ratio of 4 mL of OLAM to 1 mL of OLAC with a total of 40 mL of surfactants within a Ni 0.8 Co 2.2 S 4 synthesis was found to give monodisperse, sphere-like particles. TEM images of a Ni 0.8 Co 2.2 S 4 synthesis using 40 mL of surfactants but at varied volume ratios exhibited mixed morphologies in OLAC only (Figure S8a), agglomerated particles with high OLAM ratios (Figure S8b,c), and polydisperse particles with equal amounts of OLAM and OLAC (Figure S8d).…”
Section: Synthesis Resultsmentioning
confidence: 96%
“…Previous work has shown that OLAM and OLAC may both act as reducing agents as well as surface protection and can impact the growth of nanoparticles affecting their size and shape. 28,29,39 An optimal ratio of 4 mL of OLAM to 1 mL of OLAC with a total of 40 mL of surfactants within a Ni 0.8 Co 2.2 S 4 synthesis was found to give monodisperse, sphere-like particles. TEM images of a Ni 0.8 Co 2.2 S 4 synthesis using 40 mL of surfactants but at varied volume ratios exhibited mixed morphologies in OLAC only (Figure S8a), agglomerated particles with high OLAM ratios (Figure S8b,c), and polydisperse particles with equal amounts of OLAM and OLAC (Figure S8d).…”
Section: Synthesis Resultsmentioning
confidence: 96%
“…Precursor selection is key to achieving phase and shape selectivity as well controlling particle size in solution. Successful synthesis requires precursors and conditions that favor the nucleation and growth of the desired, multinary phase, often in a series of multiple steps, while suppressing the nucleation and preventing the runaway growth of competing binaries or lower order phases and impurities. With this in mind, we resorted to metal thiocyanates as precursors to simultaneously introduce the desired Sn, Pn (Sb or Bi) and S elements.…”
Section: Resultsmentioning
confidence: 99%
“…The position of these two peaks and the I d /I g ratio of 0.8957 suggests the transformed OA could be nanocrystalline graphite. 56,57,48 Recalling Figure 5(b) where OA is completely decomposed at 350 °C (no carbonaceous residue observed by color) in N 2 , it is understood that catalysis of GNP modifies the decomposition of OA in N 2 by producing residual nanocrystalline graphitic carbon.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Besides the mass change, its first order derivative of mass change with respect to the temperature is also presented, which is known as derivative thermogravimetry (DTG). DTG shows the mass loss rate at a given temperature, and the peaks indicate thermal events such as material evaporation, pyrolysis, decomposition, and/or chemical reaction with volatile species generation . When annealed in air, the ink sample shows mass loss mainly at ∼240 and 284 °C with two distinct peaks, and when heated in air, the ink shows four peaks at ∼176, 244, 430, and 600 °C.…”
Section: Resultsmentioning
confidence: 99%